Taá¸¥lÄ«l Akhá¹Äâ€™ al-Aá¹£wÄt al-Ê¿Arabiyyah fÄ« MahÄrah al-QirÄâ€™ah - Hamidah, Maratun; S, Yelfi Dewi (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This letter was submitted on the topic â€œAnalyzing the Errors of Arabic Sounds in Reading Skill.â€ The object of this research is the students other than the department of Arabic language education at the state Islamic University of Bukittinggi are not able to pronounce the letters of the convergent sound, and then the department of Arabic language education at the state Islamic university of Bukittinggi, who are not able to pronounce all the alphabets. Then the type of this research is qualitative and descriptive. The data of this research are the result of the recording of students who read Arabic texts, and the data sources for this research are the students of the college of education and educational science, other than the department of teaching Arabic, using the snowball sampling technique. The research results show that the wrong form in reading Arabic texts is the changes in the sound of the analysis of errors. Analysis of student mistakes in the letter Ø¸ becomes the letter Ø² and Ø¬, the letter Ø·, becomes the letter Øª, the letter Ø¶ becomes the letter Ø¯, the letter Ø« becomes the letter Ø³, Ø´, and the letter Ø° becomes the letter Ø², Ø¬, the letter Ø becomes the letter Ù‡, the letter Ø² becomes the letter Ø³, the letter Ø¹ becomes the letter Ø¡, and the letter Ø´ becomes the letter Ø³.Ù‡Ø°Ù‡ Ø§Ù„Ø±Ø³Ø§Ù„Ø© Ù‚Ø¯Ù…Øª Ø¨Ù…ÙˆØ¶ÙˆØ¹ "ØªØÙ„ÙŠÙ„ Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©".Â  Ø§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø·Ù„Ø§Ø¨ ØºÙŠØ± Ù‚Ø³Ù… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¬Ø§Ù…Ø¹Ø© Ø¨ÙˆÙƒÙŠØª ØªÙ†Ø¬ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© ØºÙŠØ± Ø§Ù„Ù‚Ø§Ø¯Ø±ÙŠÙ† Ù„Ù†Ø·Ù‚ Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ØªÙ‚Ø§Ø±Ø¨Ø© ØµÙˆØªÙ‡Ø§ Ùˆ ØºÙŠØ± Ø§Ù„Ù…Ø³ØªØ·ÙŠØ¹ÙŠÙ† ÙÙŠ Ù†Ø·Ù‚ Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© ÙƒÙ„Ù‡Ø§. Ø«Ù… Ù†ÙˆØ¹ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù†ÙˆØ¹ÙŠ Ùˆ ÙˆØµÙÙŠØŒ Ùˆ Ø¨ÙŠØ§Ù†Ø§Øª Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù†ØªØ§Ø¦Ø¬ ØªØ³Ø¬ÙŠÙ„Ø§Øª Ø£Ùˆ ØªØ³Ø¬ÙŠÙ„Ø§Øª ØµÙˆØªÙŠØ© Ù„Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† ÙŠÙ‚Ø±Ø¤ÙˆÙ† Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙ…ØµØ§Ø¯Ø± Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„ÙƒÙ„ÙŠØ© Ø§Ù„ØªØ±Ø¨ÙŠØ© ÙˆØ¹Ù„ÙˆÙ… Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªØ®ØµÙˆØµÙŠØ© Ù„ØºÙŠØ± Ù‚Ø³Ù… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ØªÙ‚Ù†ÙŠÙ‚ÙŠØ© Ø£Ø®Ø°Ø§ Ø§Ù„Ø¹ÙŠÙ†Ø§Øª Ù…Ù† ÙƒØ±Ø© Ø§Ù„Ø«Ù„Ø¬. Ù‡Ø°Ù‡ Ø§Ù„Ù†ØªØ§Ø¦Ø¬ ØªØ¨ÙŠÙ† Ø£Ù† Ø§Ù„Ø´ÙƒÙ„ Ø§Ù„Ø®Ø·Ø£ ÙÙŠ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù‡Ùˆ Ø§Ù„ØªØºÙŠØ±Ø§Øª ÙÙŠ ØµÙˆØª Ø§Ù„ØØ±ÙˆÙ. Ø£Ù…Ø§ Ø§Ù„Ø´ÙƒÙ„ Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙŠÙƒÙˆÙ† ÙÙŠ ØµÙˆØª Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ØªØÙ„ÙŠÙ„ Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙŠÙƒÙˆÙ† ÙÙŠ ØØ±Ù Ø§Ù„Ø¸Ø§Ø¡ "Ø¸" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø²Ø§ÙŠ Ùˆ Ø§Ù„Ø¬ÙŠÙ… "Ø²ØŒØ¬"ØŒ ÙˆØØ±Ù Ø§Ù„Ø·Ø§Ø¡ "Ø·" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„ØªØ§Ø¡ "Øª"ØŒ ÙˆØØ±Ù Ø§Ù„Ø¶Ø§Ø¯ "Ø¶" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø¯Ø§Ù„ "Ø¯"ØŒÂ  ÙˆØØ±Ù Ø§Ù„Ø«Ø§Ø¡ "Ø«" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø³ÙŠÙ† Ùˆ Ø§Ù„Ø´ÙŠÙ† "Ø³ØŒ Ø´"ØŒÂ  ÙˆØØ±Ù Ø§Ù„Ø°Ø§Ù„ "Ø°" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø²Ø§ÙŠ Ùˆ Ø§Ù„Ø¬ÙŠÙ… "Ø²ØŒØ¬"ØŒ ÙˆØØ±Ù Ø§Ù„Ø®Ø§Ø¡ "Ø®" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„ØØ§Ø¡ "Ø"ØŒ ÙˆØØ±Ù Ø§Ù„ØØ§Ø¡ "Ø" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ù‡Ø§Ø¡ "Ù‡"ØŒ ÙˆØØ±Ù Ø§Ù„Ø²Ø§ÙŠ "Ø²" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø³ÙŠÙ† "Ø³"ØŒ ÙˆØØ±Ù Ø§Ù„Ø¹ÙŠÙ† "Ø¹" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø£Ù„Ù "Ø£"ØŒ ÙˆØØ±Ù Ø§Ù„Ø´ÙŠÙ† "Ø´" ÙŠØµØ¨Ø ØØ±Ù Ø§Ù„Ø³ÙŠÙ† "Ø³".